Does tranexamic acid prevent the expansion of hematoma in spontaneous intracerebral hemorrhage in a randomized controlled trial? - Panjaburee, Jedsada; Vaniyapong, Tanat (Thai Journal of Neurological Surgery, 2025)
Background: Hypertensive spontaneous intracerebral hemorrhage (ICH) is common cause of death and disability in Thailand. Tranexamic acid (TXA) showed its efficacy in reduction of number of patients with ICH expansion but in hemorrhagic stroke the evidence is limited. This study aims to assess the effect of tranexamic acid (TXA) on hematoma growth of patients with spontaneous ICH compared to a placebo. Methods: A triple-blinded randomized controlled trial was conducted to evaluate the efficacy of combining a rapid administration of TXA with combination with strict blood pressure control to prevent hematoma expansion on patients with acute hypertensive ICH (< 24 hours). A total of 40 participants were included. Twenty patients were assigned to receive tranexamic acid and 20 to placebo. Results: For primary outcome, despite tranexamic acid group tended to have less expansion risk (15% for tranexamic acid group versus 25% for placebo group, RR 0.71) but had no statistically difference (p-value 0.695). None of patient had surgical treatment, death, or serious adverse event. Conclusions: This study showed tranexamic acid did not affect stabilizing the hematoma over placebo in spontaneous intracerebral hemorrhage patients in small volume of hematoma (< 30 ml.)